Adjacency Pairs Analysis In "Red Riding Hood's" Movie - Fitriana, Ghea Aprilia; , Dra. Malikatul Laila, M. Hum; , Agus Wijayanto, Ph. D. (2013)
In our life, we always convey message by two patterns. There are automatic pattern and mix of different sequence pattern. The objectives of this research are to describe the way characters in Red Riding Hood movie show pattern of adjacency pairs and the language function of the utterances forming adjacency pairs in the dialogue. The data are the conversation in Red Riding Hood movie. In collecting the data, the writer applied the documentation and observation. The theories used are the Levinson theory. The several steps are done to analyze the data. In analyzing the conversations to get the pattern of adjacency pairs, the steps are: selecting the movie, download the manuscript of the movie, watching the movie and take a note the dialogues that content directive utterance, identifying the directives utterances that show a pair of statement and response into one data or group. This results show that (1) the patterns of adjacency pairs used in Red Riding Hood movie are: automatic pattern and mix of different sequence, and (2) the language functions used in the dialogue of Red Riding Hood Movie are: request, question, complain, offer, threat, hold.